Directions of Energy Development in the Republic of Uzbekistan - Saitkamolov Mukhammadkhuja Sobirkhuja ugli (Periodica Journal, 2022)
The article presents the directions of development of the energy sector in the Republic of Uzbekistan and the tasks for their improvement. The structure of priorities is based on the current state of the energy sector and the measures outlined in the concept until 2030.
Keywords: energy; industry; concept; development